Ambulatory Arrhythmia Monitoring in Pregnant Patients with Palpitations - Cruz, Meredith O.; Hibbard, Judith U.; Alexander, Tamika; Briller, Joan (American Journal of Perinatology, 2013)
Objective To assess the frequency of rhythm disturbances (RDs) obtained following placement of a Holter monitor or an event loop recorder (ERT) in patients referred to cardiologists.Study Design Ninety-six gravidas were referred to the cardiology clinic for palpitations, syncope, or dizziness and had Holter monitoring or ERT after a baseline electroencephalogram. Arrhythmias were classified by severity.Results Gestational age at referral was 22.6 weeks ± 8.3 days. Sixty-five patients had ERTs performed, and 19 had Holter monitors. Seventy-six percent had benign arrhythmias. In our ERT cohort, history of arrhythmias showed a fourfold increase in serious RD during gestation (odds ratio [OR] 4.7, 95% confidence interval [CI] 1.1 to 20.3, p = 0.01); obesity (body mass index >30) had a fourfold increased risk (OR 4.0, 95% CI 1.0 to 1, p = 0.03). Serious RD did not result in greater chance of cesarean delivery or induction of labor, or a newborn with arrhythmias.Conclusion Most pregnant women with palpitations have benign arrhythmias. ERT appears to be a better method of diagnosis in pregnant women.
Keywords: palpitations; arrhythmias; pregnancy; event recorder tracing; Holter monitor